INOVASI KEMASAN DAN PENGGUNAAN PRODUK GULA AREN UNTUK MENINGKATKAN OMSET PASAR UMKM DI DESA KEKAIT KECAMATAN GUNUNGSARI KABUPATEN LOMBOK BARAT - Mubayyinah, Istiharatul; Aulia, Tasya Nurul; Mazlin, Mazlin; Effendi, Salma Putri; Rahmani, Nadia; Putra, I Ketut Eka; Hayaza, Saosan Alamuna; Tharamatha, Dimas Ezra Andrew; Nurdianisa, Maistarah Putri; Melanie, Tasya Septiana (Universitas Mataram, 2023)
Desapreneur Integrated Real Work Lecture (KKN) is a community service activity involving students as participants and lecturers as mentors focusing on the desapreuner theme. KKN activities in Kekait Village, Gunungsari sub-district, West Lombok district for 45 days focused on product innovation and marketing of Micro, Small and Medium Enterprises (MSMEs) products. The problems encountered in Kekait village are marketing which is still limited to around the village, packaging that only uses large sizes such as hundreds of grams and kilos, and a lack of awareness to brand a product. Departing from these problems, it is deemed important to provide assistance regarding packaging innovation and the use of palm sugar products to one of the MSME actors who has the potential to expand marketing. The purpose of this research is to increase MSME sales turnover by expanding the palm sugar market in Kekait village, Gunungsari sub-district, West Lombok district. The method used is interviews in data collection and using mentoring methods in its implementation. The benefit of the research is to increase innovation and competitiveness of palm sugar products in Kekait village, Gunungsari sub-district, West Lombok district. Suggestions from researchers to the Kekait Village community are that it is hoped that every MSME actor will increase his confidence in their products.